Variation of Thermal Infrared Brightness Temperature Anomalies in the Madoi Earthquake and Associated Earthquakes in the Qinghai-Tibetan Plateau (China) - Yang, Xing; Zhang, Tie-bao; Lu, Qian; Long, Feng; Liang, Ming-jian; Wu, Wei-wei; Gong, Yue; Wei, Jia-xi; Wu, Jia (Frontiers in Earth Science, 2022)
We processed MODIS data received from ground receiving stations into the spatial range of the Tibetan Plateau (China) and the eastern margin of the plateau, and then 283 K was set as the threshold value to remove the area covered by clouds. The monthly background field was calculated based on the 17 years data, then we obtained the spatial BT(Brightness Temperature) anomaly of the current month by deducting the background field. Furthermore, the BT anomaly curves for secondary tectonic blocks in the plateau were calculated. The data indicates that since June 2020, the BT radiation within the Tibetan Plateau began to increase abnormally, starting from the western part of the study area and expanding eastward to cover the entire plateau. In January 2021, such an anomaly was seen again, extending to the Sichuan-Yunnan Block in the easternmost part of the study area in April. With the ongoing anomaly, a series of moderate and strong earthquakes occurred in the Tibetan Plateau, and finally on May 22, 2021, the M7.4 earthquake struck the Madoi County. Moreover, according to the internal BT time series curves of the different secondary tectonic blocks, the BT has increased simultaneously since the beginning of 2020. A twofold standard deviation was found in the middle-east segment of the Bayanhar Block and the Qiangtang Block in October 2020, and an almost twofold standard deviation was found in March, while a twofold standard deviation was found in the Sichuan-Yunnan Block in April 2021. The occurrence of earthquakes before the Madoi earthquake coincided with an upward trend in the time series curve. The spatial anomaly of BT over the Tibetan Plateau disappeared and the BT time series curve dropped drastically after Madoi earthquake. The spatial anomaly of BT and the time series curve development both coincide with the occurrence of earthquakes, and are consistent with the generation of tectonic stress in the Tibetan Plateau. Our study documents that thermal infrared BT radiation reasonably reflects regional stress development and enables the detection of anomalies prior to moderate and strong earthquakes.